HYDROXYL IN OLIVINES FROM MANTLE XENOLITHS IN KIMBERLITES OF THE SIBERIAN PLATFORM - Matsyuk S.S.; Langer K. (My University, 2004)
From a total of 335 olivine crystal grains, crystallographically orientated platelets and, where possible, parallelepipeds were prepared, chemically analysed by electron microprobe, examined under the polarisation microscope, and studied by polarised FTIR microscope-absorption-spectrometry in the OH vibrational range, 3,000–3,800cm–1. The 335 crystal grains were extracted from 174 different specimens of Yakutian upper mantle material, including 97 xenoliths that represent all the rock types occurring in all the kimberlites of the Siberian shield. The other specimens were mega- and macrocrysts or inclusions in diamonds and garnets. Analysis of the polarised OH-spectra allowed distinction between hydroxyl in non-intrinsic separate inclusions, NSI, and in isolated local or condensed extended defects, intrinsic to the olivines, ILD or CED, respectively. As the two latter types cannot be distinguished by vibrational spectroscopy, and as they are presumably interconnected by intracrystalline condensation reactions of the type n [ILD][CED]n, we propose to symbolise them as [ILD/CED]. Of the total of 70 polarised OH-bands that were found in the whole set, 17 are caused by NSI, 53 by [ILD/CED]. Total mean integrated OH-band intensities, (̄int)total with ̄int=(||a+||b+||c)int/3, were determined from the spectra. They yielded the contents of structurally unallocated water, using the recent calibration of the IR-method (Bell et al. 2003).
Keywords: olivine